WAWASAN PEMBERANTASAN KORUPSI DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Bashori Alwi; A. Hirzan Anwari; Arman Arman (Fakultas Agama Islam Universitas Nurul Jadid, 2021)
Almost every day, issues and news about corruption become part of several headlines in newspapers, or become a theme raised in television media in this country. This fact indicates that, today Indonesia is still unable to escape from a culture of corruption that is getting stronger and running systemically. Although it is not proclaimed as an Islamic state, Indonesia is listed as a country with a Muslim majority. Even so, the quantity of diversity is not directly proportional to the moral quality and practice of religion which explicitly states, both in the Koran and al-Sunnah, that it prohibits actions that harm others, let alone the State. Because Indonesia is dominated by a Muslim majority, whether it is recognized or not, the perpetrators of corruption in this country are mostly Muslims. This article will discuss the discourse on the eradication of corruption as stipulated in Law Number 20 of 2001 and in Islamic law. By using literature research methods and descriptive analysis of the sources of positive law and Islamic law, this article produces several findings, namely; 1) efforts to eradicate corruption as regulated in Law Number 20 of 2001 are carried out with physical punishments such as fines and a maximum sentence of life which does not provide a deterrent effect to the perpetrators; 2) Islam emphasizes that the eradication of corruption is carried out by means of theological-morality, namely awareness of corruptors and the provision of moral sanctions, such as being displayed to the public so as to provide an educational effect for others. From these findings, this article agrees with Mahfud MD's idea that punishment for corruptors should be carried out in the aspects of physical and moral punishment.